Alcohol-Related Diagnoses in Hospital Admissions for All Causes Among Middle-Aged and Older Adults: Trends and Cohort Differences From 1993 to 2010. (December 2015) - Sacco, Paul; Unick, George Jay; Kuerbis, Alexis; Koru, A. Güneş; Moore, Alison A.
Objective: This aim of this study was to characterize trends in alcohol-related hospital admissions among middle-aged and older adults from 1993 to 2010 in relation to age, gender, race, and cohort membership.Method: This study utilized repeated cross-sectional data from the Nationwide Inpatient Sample. Using alcohol-related classified admissions, yearly rates and longitudinal trends of alcohol-related inpatient hospitalizations based on age, period, birth cohort, gender, and race were estimated.Results: Among those aged 45 and older, admissions rose from an estimated 610, 634 to more than 1, 134, 876, and rates of any alcohol-related diagnosis also increased from 1993 to 2010. Rates for men were consistently higher than women, and rates for Blacks were higher than Whites. Age was associated with decreasing rates, but post–World War II cohorts displayed higher rates over time.Discussion: Rates of alcohol-related admissions are increasing among adults above age 45, which may be a function of cohort effects. Training the health care workforce is crucial to respond to this trend.